Pertobatan Ekologis Menurut Ensiklik Laudato Si dalam Menanggapi Pelanggaran Martabat Alam Dinamis dan Metaforis di Kabupaten Nunukan, Kalimantan Utara - Satria Satria; Bernard Subang Hayong; Antonio Camnahas (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to explain the concept of ecological repentance according to the encyclical Laudato Si in responding to violations of nature that occur in Nunukan Regency, North Kalimantan. This study also aims to understand the call of the encyclical Laudato Si that it is important to protect and preserve nature as part of human life. This study is a development of philosophical reflection on dynamic and metaphorical nature by FX. Eko Armada Riyanto, in his book entitled Menjadi-Mencintai: Berphilsafat Theologis Sehari-hari and also as a reflection on the call of the encyclical Laudato Si that the universe is a common home that must be maintained for the sake of creating universal fellowship in God. Departing from Armada Riyanto's philosophical reflection, the author is moved to provide further reflection on the destruction of nature that is occurring in the world today, specifically nature in Nunukan Regency, North Kalimantan. Ecological problems such as forest destruction that occurs in Nunukan Regency are the destruction of nature which is a common home as a place of fellowship of all creation. Therefore, the Church through this encyclical loudly voices ecological conversion for all believers so that with it humans can once again knit harmony with the created nature. In this paper, the author presents a philosophical study that describes nature as an entity that has great value and dignity, so that the existence of nature is not only seen as a reality of entertainment or a tool to satisfy human needs, but also as part of human life. In addition, the author also provides an understanding of the importance of ecological conversion that must begin with the awareness that created nature is God's creation that must be guarded, maintained and protected with concrete communal actions to maintain the integrity of nature in Nunukan Regency. The methodology used in this study is a qualitative method by conducting a literature study related to the theme discussed. In addition, the methodology used is a literature study of several previous studies that are also related to the theme discussed in this paper.